Financial inclusion new measurement and cross-country impact. assessment. - Cyn-Youn,Park (Metro Manila, Philippines Asian Development Bank, 2018)
Financial inclusion one of the pillars of the global development agenda aids inclusive growth and economic development. This paper introduces a new index of financial inclusion for 151 economies using principal component analysis to compute weights for aggregating nine indicators of access, availability, and usage. It then assesses the impact of financial inclusion on poverty and income inequality. The results indicate that high and middle high income economies with high financial inclusion have significantly lower poverty, while no such relation exists for middle-low and low-income economies. The nonlinearities in the cross-country determinants and impacts of financial inclusion on poverty and income inequality across income groups are important to choosing appropriate policies for achieving inclusive growth in different development stages.
Keywords: Economics; Poverty; Industrial policy -- Asia; Electronic books